2018
DOI: 10.1615/jpormedia.v21.i5.20
|View full text |Cite
|
Sign up to set email alerts
|

A Porous Media Model of Alveolar Duct Flow in the Human Lung

Abstract: Prediction of air flow in the human lung is of great interest for many physiological applications. Recent advances in modeling such flows using computational fluid dynamics have included the development of porous media-based approaches that consider the small-scale airways and alveoli as a porous domain. This article presents a derivation of the governing equations relevant to flow in an alveolated duct based on the theory of volume-averaging as well as their closure. It is shown that the momentum closure prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It is noted that unlike the work of Elhalwagy and Straatman [33], the specific heats c p,i are based on absolute temperature herein and not referenced at 0 • C. As elaborated above, there is no need for closure coefficients for the respiration source terms and hence, closure is only needed for K, c E and h f s . In regards to the permeability and Forchheimer tensors, reviewing the works of Whitaker [43] and DeGroot and Straatman [44,45], a permeability tensor may be regarded as diagonal and symmetric for a REV that has a symmetric 'pore geometry' for all three directions. Herein, the characteristic microscopic length l of the averaging process is based on the average diameter of produce d P and may define the 'pore geometry' to be 3D symmetric as variation of this average length may be neglected between different directions.…”
Section: The Porous Continuum Modelmentioning
confidence: 99%
“…It is noted that unlike the work of Elhalwagy and Straatman [33], the specific heats c p,i are based on absolute temperature herein and not referenced at 0 • C. As elaborated above, there is no need for closure coefficients for the respiration source terms and hence, closure is only needed for K, c E and h f s . In regards to the permeability and Forchheimer tensors, reviewing the works of Whitaker [43] and DeGroot and Straatman [44,45], a permeability tensor may be regarded as diagonal and symmetric for a REV that has a symmetric 'pore geometry' for all three directions. Herein, the characteristic microscopic length l of the averaging process is based on the average diameter of produce d P and may define the 'pore geometry' to be 3D symmetric as variation of this average length may be neglected between different directions.…”
Section: The Porous Continuum Modelmentioning
confidence: 99%
“…In that paper, simulation of pore level is showed in alveolate duct geometry to determine its permeability. Air flow in an alveolate duct has been shown by a theoretically based closure model [8]. Here the permeability is obtained by solving the closure problem and direct simulation of flow obtained by verifying the assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…According to Haber et al [8] the deposition of particles also depends on media porosity due to the large number of alveoli inside the human lung. Many researchers [9,10] defined it as a sponge or porous medium. Cheng [11] and Vafai et al [12] used the porous media approach for convective mass transfer in the airway and its surrounding wall tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Saini et al [14] treated the alveolar region as a biofilter and found removal efficiency of lung for nanoparticles by using generalized Navier-Stokes equations. Recently DeGroot and Straatman [9] worked on expansion and contraction of alveolar duct and assumed lung is a porous medium by using theory of volume-averaging technique for unit cell of an alveolar duct to predict permeability of human lung.…”
Section: Introductionmentioning
confidence: 99%